Estimativa dos Fluxos Superficiais de Energia Utilizando o Modelo de Superfície Noah - Timm, Andréa U. (2009)
This study aims to compare the surface flows of energy (sensibleheat and latent) obtained from Candiota07 micrometeorologicalexperiment with the results estimated by the Noah surface model.According to the results, the Noah surface model presents a goodagreement with observed data, except for the flow of latent heat duringthe night.